An empirical model and sensitivity analysis for silica oxide in enhanced oil recovery - Isa, N.F.M. (American Institute of Physics Inc., 2019)
Energy consumption worldwide is expected to increase in coming years. However, since the availability of new core is limited, it is important to use Enhanced Oil Recovery (EOR) methods because large amount of the original oil in place is left after the production through primary and secondary recovery. One of the interesting method in EOR is injecting nanofluids. Silica oxide in a size of nanoparticle was chosen for this paper. A mathematical model for oil mobility by using silica oxide nanofluid is developed. Curve fitting techniques is used to produce a sustainability analysis for the properties of silica oxide. Normalized sensitivity index shows that density of nanofluids is the most important parameter in order to increase oil production. The optimal values for particle size, concentration, viscosity, density and injection rate were obtained respectively as 15nm, 0.50 wt, 0.92 cp, 1.00-g/cm3 and 0.4-ml/min in order to get 12.07 recovery factors (RF)s. Â© 2019 Author(s).